Penerapan Agile Project Management dalam Pengelolaan Startup Dakwah Digital Qara'a Indonesia - Fasya Perwata Pratama; Jesica; Alfa Laila; Hazitun Nisa (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2025)
The rapid advancement of digital technology has pushed Islamic outreach organizations to adopt more adaptive and responsive project management approaches. This study aims to examine how Agile Project Management is implemented within Qara’a Indonesia, a digital da’wah startup that develops an AI-driven Qur’an learning application, and to analyze how these practices support project effectiveness. A descriptive qualitative design was employed, using in-depth interviews, observation of digital activities, and internal documentation to collect data. The data were analyzed through reduction, presentation, and conclusion drawing, supported by source triangulation. The findings reveal that Qara’a applies core Agile principles through a distributed organizational structure, the classification of tasks into major and minor categories, priority setting based on workload, and coordination using digital tools such as Discord, Google Docs, and Notion. Short iterations, flexibility toward shifting market needs, intensive cross-division collaboration, and weekly evaluations demonstrate strong alignment with Agile elements such as sprints, continuous updates, and retrospectives. These practices enhance execution speed, maintain focus on key priorities, and accelerate feature development. The study provides important practical implications for strengthening innovation sustainability within technology-based da’wah services. Its novelty lies in offering one of the first analyses of Agile implementation in the context of a digital da’wah startup a domain that remains underexplored in existing literature.